Realization of malignant potential of human glioblastoma mitochondria in immunodeficient animals - O. I. Kit; E. M. Frantsiyants; A. I. Shikhlyarova; I. V. Neskubina (Исследования и практика в медицине)
Purpose. Obtaining extracranial diﬀuse tumor foci of glioblastoma in Balb/c Nude mice by implantation of mitochondria isolated from human glioblastoma.Material and methods. Human glioblastoma mitochondria were isolated using diﬀerential centrifugation in a high speed refrigerated centrifuge. Mitochondrial samples were diluted with 0.9 % NaCl solution to a protein concentration of 3 mg of protein in 0.4 ml of saline. Balb/c Nude mice (N = 6) were intraperitoneally transplanted with freshly isolated glioblastoma mitochondria at the rate of 3 mg of protein per 1 animal in 0.4 ml of physiological solution. Male mice of Balb/c Nude line (N = 4), which were injected once intraperitoneally with 0.4 ml of physiological solution, served as control. All animals were euthanized by guillotine decapitation 17-21 days aﬅer parenteral implantation of mitochondria isolated from glioblastoma.Results. Speciﬁc changes in the spleen structure were revealed (N = 4): the formation of strands of cells resembling glioblastoma multi-forme was observed in multiple ﬁelds of vision. The initiation of diﬀuse growth of glioblastoma cells in the stromal part of the red pulp of the spleen was evidenced by the expression of GFAP and ki-67, which were also recorded in the tumor preparation of the patient with glioblastoma. Morphological examination of the mesentery and lymph nodes revealed multiple areas with atypical cells resembling glioblastoma multiforme, localized in ﬁbrous septa and sinuses. Stained granules with the corresponding immunohistochemical proﬁle, GFAP and ki-6, were clearly deﬁned in the mesentery and lymph node of a Balb/c Nude mouse (N = 6) aﬅer transplantation of human glioblastoma mitochondria. An additional study of the immunophenotype of cells in the spleen, mesentery, and lymph nodes of Balb/c Nude mice by the generally accepted marker S100 leﬅ no doubt about the induction of malignant growth aﬅer transplantation of mitochondria isolated from human glioblastoma.Conclusions. Parenteral implantation of mitochondria isolated from human glioblastoma in male Balb/c Nude mice Might cause the growth and development of extracranial foci of glioblastoma in animals.